Transgenic citrange troyer rootstocks overexpressing antimicrobial potato snakin-1 show reduced citrus canker disease symptoms - Conti, Gabriela (2020)
Citrus canker is a major disease caused by Xanthomonas citri pv. citri. Snakin-1 is an antimicrobial peptide, which was previously shown to be effective against different bacterial and fungal diseases in potato, wheat and lettuce when expressed in transgenic plants. We generated transgenic Citrange Troyer citrus rootstocks constitutively expressing this peptide and 5 different transgenic lines were challenged against virulent X. citri isolates. Challenge assays conducted in vitro using detached leaves and in planta by infiltration revealed a significant reduction of the number and size of canker lesions in some of the transgenic lines.